Strengthening al-qur'an literacy through islamic education for students at sd ashabul kahfi pk sidoharjo - Esa Shofa Kamila Salsabila; Amir Mukminin; Riky Supratama; Hanura Dewi Fadilah; Siti Qomala Khayati (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research examines the strengthening of Al-Qur’an literacy through Islamic Religious Education (PAI) learning at SD Ashabul Kahfi PK Sidoharjo. Al-Qur’an literacy in this context goes beyond the mechanical ability to read Arabic script; it also includes the comprehension of meaning, internalization of Qur’anic values, and their application in everyday life. Employing a qualitative approach with data collected through interviews, observation, and document analysis, the study reveals that Qur’anic literacy reinforcement is primarily implemented through the habituation of reading the Qur’an before daily learning activities. This program is designed to prepare students’ mental and spiritual readiness while embedding religious values into their daily routines, serving as a preventive measure against moral decline in the era of globalization. Key supporting factors in the implementation of the program include strong collaboration among school stakeholders—teachers, principals, and administrative staff—as well as active parental involvement. These elements contribute to a school environment that consistently promotes Qur’anic engagement and values-based education. However, a notable challenge remains: the lack of awareness among some students regarding the deeper significance of Qur’anic learning. This is reflected in the low intrinsic motivation and passive participation observed during Qur’an reading sessions. Despite this, the program has shown measurable effectiveness in enhancing students’ Qur’anic reading fluency and comprehension, while also positively contributing to their character formation. The educational approach adopted by the school is oriented toward Rabbani values those centered on spiritual consciousness and moral excellence. Through consistent Qur’an-based character education, students are encouraged to develop noble traits such as discipline, humility, patience, and emotional regulation. In conclusion, the Qur’anic literacy program at SD Ashabul Kahfi PK Sidoharjo presents a valuable model for integrating religious instruction with holistic character education, contributing meaningfully to the school’s broader mission of shaping spiritually resilient and morally upright individuals.